Sintomas dispépticos e retardo do esvaziamento gástrico de sólidos em pacientes com doença de Crohn em remissão - Nóbrega, Ana Carolina Mello (2011)
Patients with Crohn’s disease have been shown to present dyspeptic symptoms more frequently than the general population. Some of these symptoms could be related to some degree of motility disorders. Our objectives were to investigate whether gastric emptying of solids in patients with inactive Crohn’s disease is delayed and to determine the relationships between gastric emptying and dyspeptic symptoms in inactive Crohn’s disease. Twenty-six patients with inactive Crohn’s disease, as defined by a Crohn’s Disease Activity Index (CDAI) < 150, underwent a gastric emptying test by breath test using 13C octanoic acid coupled to a solid meal and answered a validated questionnaire (The Porto Alegre Dyspeptic Symptoms Questionnaire) to assess dyspeptic symptoms. Patients were divided in two groups: without dyspepsia (total score < 6) and with dyspepsia (total score ≥ 6). The control group was composed by 14 healthy volunteers age and sex matched. Patients with Crohn’s disease had a significantly longer t 1/2 and t lag (p<0.05) than the controls. Crohn’s disease patients with dyspepsia had significantly (p<0.05) delayed gastric emptying when compared to patients without dyspeptic symptoms. When the individual symptom patterns were analyzed, only vomiting was significantly associated with delayed gastric emptying (p<0.05). There was no difference between the subgroups of patients with respect to gender, CDAI scores, disease location, clinical behavior (obstructive/obstructive) or previous gastrointestinal surgery. However, it was observed that patients in the group without dyspepsia were treated with immunosuppressants (azatioprina/6-MP) in a proportion significantly higher (p <0.05) than patients in the group with dyspepsia. In conclusion, delayed gastric emptying in inactive Crohn’s disease patients seems to be associated with dyspeptic symptoms, particularly vomiting, even without any evidence of gastrointestinal obstruction.